Comparative effectiveness of risk mitigation strategies to prevent fetal exposure to mycophenolate. Issue 8 (24th October 2019) - Sarayani, Amir; Albogami, Yasser; Elkhider, Mohannad; Hincapie-Castillo, Juan M; Brumback, Babette A; Winterstein, Almut G
Abstract : Background: In 2012, the US Food and Drug Administration approved a Risk Evaluation and Mitigation Strategy (REMS) programme including mandatory prescriber training and a patient/provider acknowledgement form to prevent fetal exposure to mycophenolate. Prior to the REMS, the teratogenic risk was solely mitigated via written information (black box warning, medication guide (MG period)). To date, there is no evidence on the effectiveness of the REMS. Methods: We used a national private health insurance claims database to identify women aged 15–44 who filled ≥1 mycophenolate prescription. To compare fetal exposure during REMS with the MG period, we estimated the prevalence of pregnancy at treatment initiation in a pre/post comparison (analysis 1) and the rate of conception during treatment in a retrospective cohort study (analysis 2). Pregnancy episodes were measured based on diagnosis and procedure codes for pregnancy outcomes or prenatal screening. We used generalised estimating equation models with inverse probability of treatment weighting to calculate risk estimates. Results: The adjusted proportion of existing pregnancy per 1000 treatment initiations was 1.7 (95% CI 1.0 to 2.9) vs 4.1 (95% CI 3.2 to 5.4) during the REMS and MG period. The adjusted prevalence ratio and prevalence difference were 0.42 (95% CI 0.24 to 0.74) and −2.4 (95% CI −3.8 to −1.0), respectively. In analysis 2, the adjusted rate of conception was 12.5 (95% CI 8.9 to 17.6) vs 12.9 (95% CI 9.9 to 16.9) per 1000 years of mycophenolate exposure time in the REMS versus MG periods. The adjusted risk ratio and risk difference were 0.97 (95% CI 0.63 to 1.49) and −0.4 (95% CI −5.9 to 5.0), respectively. Sensitivity analyses on the estimated conception date demonstrated robustness of our findings. Conclusion: While the REMS programme achieved less pregnancies at treatment initiation, it failed to prevent the onset of pregnancy during treatment. Enhanced approaches to ensure effective contraception during treatment should be considered.